(untitled) (SCIENCE TIME JOURNAL, 2025)
This article explores the manifestation of postmodern aesthetics in 21st-century Uzbek and Turkish novels through a comparative literary analysis. Focusing on narrative strategies, intertextuality, metafiction, fragmentation, irony, and the blending of historical and fictional elements, the study examines how contemporary writers from both literary traditions reinterpret national identity, cultural memory, and individual experience in a globalized context. The research highlights both shared tendencies—such as the deconstruction of grand narratives and experimentation with form—and distinctive features shaped by each country’s historical, social, and cultural background. By comparing selected Uzbek and Turkish novels, the article reveals how postmodernism functions not merely as an imported literary trend, but as a dynamic aesthetic framework adapted to local realities. The findings contribute to a deeper understanding of cross-cultural literary dialogue and the evolving nature of postmodern prose in Central Asian and Anatolian literature.